The Mediating Role of Social-Emotional Learning in the Relationship Between Emotional Intelligence and Students' Self-Confidence in Islamic Education - Muh Syahrul Sarea; Muh Bachtiar Aziz; Sulaeman; Faisal (PT Mattawang Mediatama Solution, 2026)
The dominance of cognitive-oriented and dogmatic instruction in Islamic Religious Education (PAI) frequently provokes academic anxiety, causing students to remain passive despite possessing adequate emotional regulation. This study aims to investigate the mediating role of Social-Emotional Learning (SEL) in the relationship between Emotional Intelligence (EI) and students' self-confidence in religious classrooms. Employing an explanatory cross-sectional survey design, data was collected from 78 high school students selected through purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a 5,000-subsample bootstrapping procedure. The results indicate that EI has a significant direct effect on both SEL and self-confidence. However, the key finding confirms that SEL acts as the most dominant predictor and serves as a complementary partial mediator in the relationship between EI and self-confidence. This study concludes that internal emotional regulation (EI) is a necessary but insufficient condition to generate self-confidence without a psychologically safe classroom ecosystem. Practically, the integration of SEL deconstructs the religious classroom from a mere space for theological dogma transfer into an inclusive dialogic space that aligns with the core values of tazkiyatun nafs (purification of the soul).